Faculty Of Computer Systems & Software Engineering teaching workload distribution system using ERP - Nik Intan Syahiddatul Ilani, Jailani (2018)
Teaching Workload Distribution System using ERP is developed for Faculty of Computer Systems and Software Engineering, Software Engineering department. This proposed system will be used by the head of SE department as an admin. This system allows the head of SE department to manage the workload distribution in a more effective way. The system allows admin to manage and update the lecturer profile. Besides, admin will manage the subject profile for a division based on the workload given. Admin will also manage the subject load distribution and the workload of the lecturers. Then, the admin can obtain a report of the teaching workload distribution. Method used in developing this system is using Rapid Application Development (RAD) as a methodology because this method has flexible phase which the developer can make a change or any improvement to the system during the development phase. In addition, the system has to be done in a short period of time; within six months. This method is the best method to be used for the project. As a conclusion, this system is an advantage to the head of SE department that help to reduce the workload and easier in making the decision.